La représentation paradoxale du chemin de fer chez Dickens : fantastique et mythe au service d’une peinture de la modernité dans Dombey and Son (1848) et « No. 1 Branch Line. The Signal-Man » (1866) - Françoise Dupeyron-Lafay (Cahiers Victoriens et Edouardiens)
With George Cruikshank’s famous engraving London Going out of Town. The March of Bricks and Mortar (1829), that gives a nightmare, fantastic image of the ravages of urbanization, we can notice the innovative resort to the Gothic to deal with modern phenomena, something as yet unprecedented in the arts, and a device that will also be used by Dickens in the 1850s and 60s to evoke the railway. However, this recourse to the Gothic represents a paradox as the Gothic is supposed to belong to the dark, distant, uncivilized medieval past and it is here used to describe the new living conditions of the industrial era, and the growth of technology. Somehow, it seems logical to resort to the linguistic and symbolic tools of the uncanny to represent new, unknown and destabilizing realities, as in « The Signal-Man ». But what appears more surprising and paradoxical is the use of archaic elements, such as myth, and teratological images—as in Dombey and Son—to depict modernity. The reason may lie in the fact that trains or factories, belching fumes and staining everything about them, were seen as dangerous, all-powerful, voracious monsters and that writers were powerless in front of such disturbing, unprecedented phenomena and had to fall back on familiar, reassuring narrative techniques to come to terms with them. Describing new facts of life with old tools—this is the central paradox and the essential originality of Dickens’s fiction on the railway.